The Impact of Traumatic Brain Injury on Binaural Processing in Young and Middle-Age Adults. - Roup, Christina M.; Lander, Devan; Powell, Julie; Hoffman, Jennifer (Journal of Speech, Language & Hearing Research, 2023)
Purpose: This study examined the impact of traumatic brain injury (TBI) on selfperceived hearing and suprathreshold binaural processing in young and middleage adults. Method: Ninety-three adults with normal hearing (thresholds ≤ 25 dB HL, 250-- 4000 Hz) participated in one of four groups: 38 young adults, 23 young adults with TBI, 16 middle-age adults, and 16 middle-age adults with TBI. Selfperceived hearing difficulty was measured via questionnaires. Binaural processing was measured using dichotic word recognition, the Listening in Spatialized Noise--Sentences Test (LiSN-S), and the 500-Hz masking level difference (MLD). For each participant, a composite binaural processing (CBP) score was calculated to obtain a global metric of binaural processing performance. The CBP was composed of six measures from the three behavioral tests, including the S0N0 and SπN0 thresholds from the 500-Hz MLD, the low- and high-cue speech recognition thresholds from the LiSN-S, and the free and directed recall ear advantages from the dichotic word test. Results: The middle-age TBI group reported significantly greater degrees of self-perceived hearing difficulty than the other groups. On average, the middleage TBI group performed poorer on the individual binaural processing tests; however, the differences were significant for the S0N0 and SπN0 MLD thresholds only. Results for the global metric of binaural processing revealed significantly poorer CBP scores for the middle-age TBI group compared to the other groups. Conclusions: Results demonstrate that both age and a positive history of TBI contributed to deficits in suprathreshold binaural processing. Middle-age adults with a history of TBI are at risk for experiencing presenescent deficits in suprathreshold binaural processing deficits, despite having clinically normal hearing.